The jumping SHOX gene-crossover in the pseudoautosomal region resulting in unusual inheritance of Leri-Weill dyschondrosteosis - Kant, Saartje Gijsbertje; van der Kamp, Hetty J.; Kriek, Marjolein; Bakker, Egbert; Bakker, Boudewijn; Hoffer, Mariette J. V.; van Bunderen, Patrick; Losekoot, Monique; Maas, Saskia M.; Wit, Jan M.; Rappold, Gudrun; Breuning, Martijn H. (The journal of clinical endocrinology & metabolism, 2011)
During meiosis I, the recombination frequency in the pseudoautosomal region on Xp and Yp (PAR1) in males is very high. As a result, mutated genes located within the PAR1 region can be transferred from the Y-chromosome to the X-chromosome and vice versa.Here we describe three families with SHOX abnormalities resulting in Leri-Weill dyschondrosteosis or Langer mesomelic dysplasia.In about half of the segregations investigated, a transfer of the SHOX abnormality to the alternate sex chromosome was demonstrated.Patients with an abnormality of the SHOX gene should receive genetic counseling as to the likelihood that they may transmit the mutation or deletion to a son as well as to a daughter.
First published online November 10, 2010
Gesehen am 11.07.2022